The impact of anionic polyacrylamide (APAM) on ultrafiltration efficiency in flocculation-ultrafiltration process - Zhang, Ruijun (Water science and technology : a journal of the International Association on Water Pollution Research, 2017)
With the purpose of improving the ultrafiltration (UF) efficiency, anionic polyacrylamide (APAM) has been used as a coagulant aid in the flocculation-UF process. In this study, the impact of APAM on UF efficiency has been investigated with regard to membrane fouling, membrane cleaning and effluent quality. The results indicated that the optimal dosage of APAM had positive impacts on membrane fouling control, membrane cleaning and effluent quality. According to the flux decline curve, scanning electron microscopy and contact angle characterization, the optimal dosage of APAM was determined to be 0.1 mg/L coupled with 2 mg/L (as Al3+) poly-aluminium chloride. Under this optimal condition, membrane fouling can be mitigated because of the formation of a porous and hydrophilic fouling layer. APAM in the fouling layer can improve the chemical cleaning efficiency of 0.5% NaOH due to the disintegration of the fouling layer when APAM is dissolved under strong alkaline conditions. Furthermore, with the addition of APAM in the flocculation-UF process, more active adsorption sites can be formed in the flocs as well as the membrane fouling layer, thus more antipyrine molecules in the raw water can be adsorbed and removed in the flocculation-UF process